Utilization of fiber color as indication trait for cotton hybrid seed between cytoplasmic male sterile line and restorer line - ZHAO Xiang-qian; WANG Xue-de (浙江大学学报. 农业与生命科学版)
Cotton fiber color used as an indication trait for the hybrid seed production was transferred into cytoplasmic male sterile line or its restorer in upland cotton. Mixed seeds made up from sterile line and restorer seeds in the ratio 2∶1, such as 2 brown and 1 white fuzz, were sowed in a field to produce hybrid seeds. This sow method was called in the paper mixed sowing fashion in contrast with row sowing fashion that sterile line and restorer seeds were separately sowed. The mixed sowing fashion could shorten the space distance of honeybee visiting flowers between restorer and sterile plants, and increase pollen amount on a sterile plant stigma. Finally, higher yield of hybrid seed could be obtained by more than 14% over check, due to higher rate of effective boll and lower rate of aborted seed of sterile plants in the mixed sowing fashion. During cotton harvest, hybrid seed cotton can be easy picked out according to fiber color of male sterile plants which is different from restorer plants. For example, if sterile-line and restorer cotton is indicated by brown and white fiber trait respectively, seeds with brown fuzz are hybrid seeds, others inbred seeds. It is feasible to utilize the fiber color as indication trait for hybrid seed production by breeding cytoplasmic male sterile line and its restorer with different fiber color trait, especially in application of colored cotton heterosis.